DINAMIKA KOMODITAS BERBASIS KEUNGGULAN LUAS LAHAN TANAMAN PANGAN KABUPATEN SUMEDANG PROVINSI JAWA BARAT - Utan Sahiro Ritonga (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2018)
This research aims to know the dynamics of commodities based on the superior of food crops area in Sumedang regency of West Java within 10 years. Through the dynamics of commodity will be known food crops most suitable for development in Sumedang District. This research used quantitative descriptive method through LQ and DLQ analysis on land area of food crops at province and district level. Based on the dynamics of commodities based on land area of food crops, it is known that soybean is the only superior commodity of Sumedang Regency, with the acquisition value LQ > 1 = 1.2 and DLQ > 1 = 2.4. Wet land paddy and sweet potato are the mainstay commodities, because of the tendency of repositioning of superior commodities into non-superior commodities. Dry land paddy and peanut are prospective commodities, due to the tendency of repositioning of non-superior commodities to be superior commodities. While small green pea, cassava, and corn are lagging commodities which fix and remain a non superior commodity of Sumedang regency of West Java. The government can minimize the transfer of commodities by intensifying the provision of farming production facilities to support extension efforts to encourage each shifting the dynamics of commodities towards a more positive.